Marketing Strategy to Increase Market Snack Sales in Street Vendor Businesses in the Penfui Area of Kupang City - Rosmiati; Bahari, Syahrul; Rolaskhi, Shadli (Yayasan Pendidikan Belajar Berdikari, 2024)
Street vendors in Kupang City, particularly in the Penfui area, play a crucial role in the local economy through the sale of traditional market snacks. However, these micro-enterprises face significant challenges, including declining sales and low digital adoption rates. This study aims to develop and implement an effective marketing strategy to increase market snack sales for street vendors in the Penfui area. Employing a mixed-method approach, we collected data from 71 street vendors and 68 consumers through in-depth interviews, surveys, and field observations over a six-month period. The research identified key issues such as limited product innovation, suboptimal pricing strategies, and inadequate promotion techniques. Based on these findings and a comprehensive SWOT analysis, we developed an integrated marketing strategy focusing on product diversification, value-based pricing, strategic location optimization, and digital promotion. This strategy was implemented with 10 pilot vendors over a three- month period. Results show a 35% increase in average daily turnover (from IDR 500,000 to IDR 675,000), a 150% growth in social media followers, and an improvement in customer satisfaction from 65% to 82%. The study demonstrates that a hybrid approach combining traditional strengths with modern digital marketing techniques, tailored to local contexts, can significantly enhance the competitiveness and sustainability of street vendors in the traditional snack market. These findings provide valuable insights for policymakers and stakeholders in developing supportive ecosystems for micro-enterprises in urban areas, contributing to both economic development and the preservation of culinary heritage.